JURIDICAL REVIEW OF LEGAL PROTECTION OF UNILATERAL EXECUTION OF THE OBJECT OF MOTOR VEHICLE CREDIT AGREEMENT BY THE FINANCING INSTITUTE OF PT. BCA FINANCE BRANCH OF SERANG (CASE STUDY OF DECISION NO.134/PDT.G/2021/PN.SRG) - Khasanah, Isvania; Agustiawan, M. Nassir; Hiffni, M. (International Journal of Multidisciplinary Research and Literature, 2025)
Every consumer must be protected by their rights, and consumer protection guarantees must receive sufficient attention. As consumers, we should be protected from various types of transaction fraud, have the right to obtain clear information, and, of course, the right not to be discriminated against. Fiduciary guarantees are used as a supporting basis for a motor vehicle agreement contract as collateral, so that when the Debtor cannot fulfill its obligations, the creditor does not make a unilateral withdrawal of the vehicle. In conducting this research, the author employs a critical analysis of theories, including agency agreement theory, legal certainty theory, and the theory of fiduciary duty. The basis of the regulation that is broken is Law Number 42 of 1999 concerning Fiduciary Guarantee and Decision of the Constitutional Court (MK) Number 18/PUU-XVII/2019, as well as the Civil Code, and is supported by several relevant studies. The methods used in this research are Normative Juridical and Literature Study in the form of qualitative research. The research was conducted at the Serang Banten District Court, where the object of the study was the court decision. The research was conducted over a period of three months, from May to July 2025. Data was obtained from primary data sources in the form of Law and Court Decision Number 134/Pdt.G/2021/PN.Srg, as well as secondary supporting materials and tertiary sources that support primary and secondary materials. This research is qualitative. The discussion in this research concerns the leasing party's unilateral withdrawal of the collateral object, in the form of a vehicle, without the Debtor's voluntary surrender or a court decision. The Debtor feels very disadvantaged by this. Creditors/Leasing have committed unlawful acts against Law Number 42 of 1999 concerning Fiduciary Guarantees a nd Constitutional Court (MK) Decision Number 18/PUU-XVII/2019. The conclusion from this research is that the leasing party has committed an unlawful act, which is regulated in Law Number 42 of 1999 concerning Fiduciary Guarantees and Decision of the Constitutional Court (MK) Number 18/PUU-XVII/2019. Suppose the collateral object in a vehicle credit agreement is unable to carry out its obligations. In that case, the creditor/leasing party may not carry out unilateral execution without a voluntary surrender from the Debtor or a court decision with permanent legal force to confiscate the collateral object.